2019
DOI: 10.1097/md.0000000000014649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga on patients with chronic nonspecific neck pain

Abstract: Background: Chronic nonspecific neck pain (CNNP) has a high prevalence and is more common among younger people. Clinical practice suggests that yoga is effective in relieving chronic pain. Objectives: This meta-analysis aimed to quantitatively summarize the efficacy of yoga for treating CNNP. Data sources: We searched for trials in the electronic databases from their inception to January 2019. English databases including PubMed, MEDLINE, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 27 publications
1
59
0
1
Order By: Relevance
“…Another systematic review without meta-analysis found that motor control exercises may not be any more effective than a standard strengthening exercise program [33]. Yoga was found to have moderate positive effects on pain (SMD −1.13 (95% CI:−1.60 to −0.66)) and disability (SMD = −0.92 (95% CI: −1.38 to −0.47)) over other treatments (mostly other exercise) for people with chronic non-traumatic neck pain [17] but the results had high heterogeneity, indicating caution is required with interpretation.…”
Section: Exercisementioning
confidence: 99%
“…Another systematic review without meta-analysis found that motor control exercises may not be any more effective than a standard strengthening exercise program [33]. Yoga was found to have moderate positive effects on pain (SMD −1.13 (95% CI:−1.60 to −0.66)) and disability (SMD = −0.92 (95% CI: −1.38 to −0.47)) over other treatments (mostly other exercise) for people with chronic non-traumatic neck pain [17] but the results had high heterogeneity, indicating caution is required with interpretation.…”
Section: Exercisementioning
confidence: 99%
“…Most of the SRs rated low or critical low quality were due to poor reporting of prespecified protocols and poor reporting of studies excluded during full-text screening, both of which are critical domains by AMSTAR 2 criteria. One SR in the mindful Mind-Body Interventions for Depressive Chronic Pain movement group did not account for risk of bias of the primary studies when interpreting the results of the review (52).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we conducted additional searches from the perspective of exercise and found that existing studies have reached a cautious conclusion: yoga can increase the cervical spine mobility of patients with chronic cervical spondylosis, but the specific strength of evidence requires subsequent research and exploration. [ 19 ] There is also evidence that stretching exercises can directly affect the range of motion of the cervical spine and that passive hamstring stretching exercises can directly affect the range of motion and balance of the cervical spine. [ 36 ] This evidence indicates that exercise may improve the cervical spine mobility of patients with cervical spondylosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many cases of intervention that use other exercise methods. [ 18 , 19 ] When compared to other aerobic or resistance exercises, [ 20 , 21 ] the advantages of mind-body exercise include its slow rhythm and stable intensity, [ 16 ] which are conducive to long-term health development. Moreover, many research results have proven that mind-body exercise is beneficial to the treatment of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%